Female space in Jane Eyre and Wide Sargasso Sea: a search for sanctuary within incarcerating spaces - Islam, Nabila (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2018.